Influence of resistance training on cardiac autonomic modulation: literature review - Barbosa, Marianne Penachini Da Costa De Rezende [UNESP] (2014)
Among the benefits provided by resistance training, its influence on cardiac autonomic modulation draws attention, given the importance of the autonomic nervous system in the control of the internal functions of the body. The objective of this narrative review was to gather information about the effects of resistance training on autonomic modulation in healthy young adults, assessed through heart rate variability. This search was performed in May 2013 in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Physiotherapy Evidence Database (PEDro), Scientific Electronic Library Online (SciELO) and Literature and Latin American and Caribbean Health Sciences (LILACS), with articles published between January 2003 and March 2013. The keywords used were: resistance training, lifting, exercise therapy crossreferenced with autonomic nervous system and parasympathetic nervous system and also the term heart rate variability. Of the 1,940 titles found, 3 complete articles were selected to compose the review. Data were analyzed qualitatively. The analysis of these studies suggests that resistance training can change the heart rate variability indices in the population of healthy young adults and that this change is due to increased vagal activity, provided by the practice of this type of training.